Elongin B-Mediated Epigenetic Alteration of Viral Chromatin Correlates with Efficient Human Cytomegalovirus Gene Expression and Replication - Jiwon Hwang (American Society for Microbiology, 2011)
ABSTRACT Elongins B and C are members of complexes that increase the efficiency of transcriptional elongation by RNA polymerase II (RNAPII) and enhance the monoubiquitination of histone H2B, an epigenetic mark of actively transcribed genes. Here we show that, in addition to its role in facilitating transcription of the cellular genome, elongin B also enhances gene expression from the double-stranded DNA genome of human cytomegalovirus (HCMV), a pathogenic herpesvirus. Reducing the level of elongin B by small interfering RNA- or short hairpin RNA-mediated knockdown decreased viral mRNA expression, viral protein accumulation, viral DNA replication, and infectious virion production. Chromatin immunoprecipitation analysis indicated viral genome occupancy of the elongating form of RNAPII, and monoubiquitinated histone H2B was reduced in elongin B-deficient cells. These data suggest that, in addition to the previously documented epigenetic regulation of transcriptional initiation, HCMV also subverts cellular elongin B-mediated epigenetic mechanisms for enhancing transcriptional elongation to enhance viral gene expression and virus replication. IMPORTANCE The genetic and epigenetic control of transcription initiation at both cellular and viral promoters is well documented. Recently, the epigenetic modification of histone H2B monoubiquitination throughout the bodies of cellular genes has been shown to enhance the elongation of RNA polymerase II-initiated transcripts. Mechanisms that might control the elongation of viral transcripts are less well studied. Here we show that, as with cellular genes, elongin B-mediated monoubiquitination of histone H2B also facilitates the transcriptional elongation of human cytomegalovirus genes. This and perhaps other epigenetic markings of actively transcribed regions may help in identifying viral genes expressed during in vitro latency or during natural infections of humans. Furthermore, this work identifies a novel, tractable model system to further study the regulation of transcriptional elongation in living cells.